Technology Transfer in Higher Education Institutions: A Philippine State Universities and Colleges’ Innovation Ecosystem Scenario - Sarita Venson B. (Discourse and Communication for Sustainable Education)
Technology transfer in Philippine State Universities and Colleges (SUCs) is a crucial component of national innovation ecosystems. The Technology Transfer Act of 2009 (RA 10055) provided SUCs with the legal framework to commercialize research outputs, yet significant challenges persist, including weak industry linkages, bureaucratic inefficiencies, and inadequate funding. This paper examines the technology transfer landscape in Philippine SUCs, with a specific focus on the Davao Region and Davao Oriental State University (DOrSU). This paper highlights barriers such as the lack of institutional capacity, limited private-sector collaboration, and regulatory constraints. It also explores futures thinking and regenerative development as strategies to enhance innovation-driven research. The findings emphasize the need for stronger policy interventions, increased funding mechanisms, and enhanced university-industry partnerships. By addressing these challenges, SUCs can become key players in regional economic development and contribute significantly to national technological advancements and Sustainable Development Goals (SDGs).